Unloading Sugar Cane, Barbados - (:unkn) unknown (The Main Library, University of the West Indies, Cave Hill Campus, Barbados is responsible for making this digital resource available., 2022)
The card shows oxcarts of sugar cane in the factory yard in Barbados. Two men stand next to the heavily laden carts. Behind them is the plantation boiling house where a number of women are seen at the door. The postcard is signed at the bottom of the picture – With love. E. Roett. Also written on the front bottom is J.R.H Seifert and Company Limited, Barbados At the back : MP 8 GBP. Made in Germany.
Landscape; Divided ; Black & White, 5 1/2 x 3 1/2 inches.
Keywords: Sugarcane; Carts and wagons; Oxen; Ox teams; Ox carts; Boilers; Sugar plantations; Sugar industry; Clothing and dress; Ox-drawn carts